Photochemical and Photobiological Reviews - Smith, Kendric C. (Plenum, 1978)
The science of photobiology is a dynamic multidisciplinary field whose relevance to the needs of man is growing more apparent each day. Publicity about supersonic transports (the SSTs) and spray cans, their possible dele terious effects on the stratospheric ozone layer, and the possible resultant consequences of enhanced solar ultraviolet radiation on man and his envi ronment have helped to focus attention on both the beneficial and the detri mental effects of light. In addition, considerable activity is currently being directed toward harnessing solar energy as one solution to the world energy crisis. Some mechanisms for accomplishing this involve photobiological systems or photochemical models based on these systems. It would thus seem that modern man has rediscovered the sun and is now actively considering new uses of light rather than thinking of light only as an aid to vision. Photobiology has become a major new scientific field. The American Society for Photobiology has divided the science of photobiology into 14 subspecialty groups: Phototechnology Chronobiology Photochemistry Photoreception Spectroscopy Vision Photosensitization Photomorphogenesis Ultraviolet and Visible Radiation Effects Photomovement Environmental Photobiology Photosynthesis Medicine Bioluminescence The goals of the science of photobiology have been divided into four categories*: "(1) The development of ways to protect organisms, including man, from the detrimental effects of light; (2) the development of ways to control the beneficial effects of light upon our environment; (3) the con tinued development of photochemical tools for use in studies of life processes; and (4) the development of photochemical therapies in